1981
DOI: 10.1113/jphysiol.1981.sp013768
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of sympathomimetic agents on gastric acid secretion by the rat stomach in vivo and in vitro.

Abstract: SUMMARY1. The action of isoprenaline on gastric acid secretion in rats with Heidenhain pouches has been compared with its action in a rat isolated stomach preparation.2. Isoprenaline (40 ,sg kg-' h-') inhibited the acid secretion in response to pentagastrin (20 ,tg kg-' h-') in conscious rats with Heidenhain pouches.3. This inhibition could be abolished by propranolol (2 mg kg-1) and butoxamine (8 mg kg-1) and partially reversed by practolol (8 mg kg-1).4. Propranolol (2 mg kg-') significantly increased the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
(17 reference statements)
2
22
0
Order By: Relevance
“…In the preceding paper (Canfield & Price, 1981) we have shown that isoprenaline stimulates acid secretion by the immature rat isolated stomach preparation, in contrast to the inhibitory effect of this and similar compounds in vivo. In this paper we present the results ofa more extensive investigation ofthe effects offl-adrenoceptor agonists on acid secretion in vitro and the action of both adrenoceptor antagonists discussed in relation to the possible mechanisms of fl-adrenoceptor-stimulated acid secretion in the isolated stomach.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the preceding paper (Canfield & Price, 1981) we have shown that isoprenaline stimulates acid secretion by the immature rat isolated stomach preparation, in contrast to the inhibitory effect of this and similar compounds in vivo. In this paper we present the results ofa more extensive investigation ofthe effects offl-adrenoceptor agonists on acid secretion in vitro and the action of both adrenoceptor antagonists discussed in relation to the possible mechanisms of fl-adrenoceptor-stimulated acid secretion in the isolated stomach.…”
Section: Introductionmentioning
confidence: 97%
“…The response to drug addition in each stomach is expressed as the secretary ratio (R) Fig. 1 A shows the log concentration-response curves for the /J2-selective agonists salmefamol and salbutamol and also the isoprenaline curve from the preceding paper for comparison (Canfield & Price, 1981), whilst Fig. 1B shows the results with the two naturally occurring catecholamines.…”
Section: Isolated Stomach Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six pieces of tissue were set up in each experiment from 2 animals. This is essentially the same apparatus previously described for use with rat stomach (Canfield & Price, 1981). The lumen of the tube contained 5 ml of a solution of composition (in mM): NaCl 136, KCI 5, 'Author for correspondence.…”
Section: Tissue Preparationmentioning
confidence: 99%